Dampak Coronavirus Disease 2019 (Covid-19) Terhadap Pengelolaan Zakat, Infaq, Dan Shadaqah (ZIS) Di Masjid Agung Pelita Samarinda - Hesti Maharani Dwi Rahayu; Moh Mahrus; Irma Yuliani (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
In the midst of the Covid-19 pandemic that has hit the world today, all aspects of life have been affected. The social sector has also been affected by the Covid-19 pandemic. This has resulted in the declining economic welfare of the Indonesian people. In Islam this welfare problem can be solved by managing and empowering the results of Zakat, Infaq, and Sadaqah (ZIS). But the Covid-19 pandemic is quite scary because it can affect people's awareness of paying Zakat, Infaq and Sadaqah (ZIS). For this reason, this study aims to determine the mechanism for the management of Zakat, Infaq and Shadaqah (ZIS) that occurred during the Covid-19 pandemic at the Great Mosque of Pelita Samarinda and to determine the impact that occurred on the management of Zakat, Infaq, and Shadaqah (ZIS) during the pandemic. Covid-19 at the Great Mosque of Pelita Samarinda. This research is a qualitative research (field research). The population in this study is the total of all Amil zakat administrators at the Great Mosque of Pelita Samarinda, a total of 54 people. In taking samples from the existing population, researchers used the Slovin formula calculation and produced a sample of 35 people. Data collection techniques used are observation, interviews and documentation. The data analysis technique used is Miles and Hubermen which starts from data collection, data reduction, data presentation, and conclusions. The results of this study indicate that the management of Zakat, Infaq and Sadaqah (ZIS) of the Great Mosque of Pelita Samarinda during the Covid-19 pandemic began with careful and careful planning. The implementation, which contains receipts and distributions, also continues to run offline and continues to comply with the health protocols recommended by the government. Supervision is also directly supervised by the board of trustees of the amil zakat management of the Great Mosque of Pelita Samarinda and BAZNAS of Samarinda City. Evaluation is carried out at the end of the activity to correct errors and correct them so that they do not recur in the future. The impact of the Covid-19 pandemic has two sides, namely a negative impact and a positive impact. The negative impacts include regulations to maintain distance and comply with health protocols, which are quite difficult for officers, friendships are also tenuous, and many people choose to pay zakat at the nearest mosque or institution, thereby reducing muzakki at the Great Mosque of Pelita Samarinda. The positive impact is the increase in the results of zakat, infaq, and shadaqah receipts in 2020. Meanwhile, in 2021 only zakat fitrah in the form of rice has increased.